2014
DOI: 10.4110/in.2014.14.5.260
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Effects of ZYM-201 on LPS-stimulated B Cells

Abstract: ZYM-201 is a methyl ester of triterpenoid glycoside from Sanguisorba officinalis which has been used for treatment of inflammatory and metabolic diseases. In this study, immunomodulatory effects of ZYM-201 on B cells were examined in vitro and in vivo. When splenocytes were activated with lipopolysaccharide (LPS), the major population which had shown an increase in cell numbers was B cells. However, when the B cells were treated with ZYM-201 after LPS activation, their cell numbers and the expression of major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…For these purposes, people are recommended to consume numerous functional foods and nutraceuticals such as taheebo, ginseng, mushrooms, and cordyceps, as well as fresh vegetables and fruits [ 5 7 ]. These are all great sources of valuable components with antioxidative, antiasthmatic, and anti-inflammatory properties such as flavonoids, saponins, alkaloids, terpenoids, and anthraquinones [ 8 11 ]. Indeed, in many different experiments with animal models, these foods have been demonstrated to display numerous beneficial pharmacological activities.…”
Section: Introductionmentioning
confidence: 99%
“…For these purposes, people are recommended to consume numerous functional foods and nutraceuticals such as taheebo, ginseng, mushrooms, and cordyceps, as well as fresh vegetables and fruits [ 5 7 ]. These are all great sources of valuable components with antioxidative, antiasthmatic, and anti-inflammatory properties such as flavonoids, saponins, alkaloids, terpenoids, and anthraquinones [ 8 11 ]. Indeed, in many different experiments with animal models, these foods have been demonstrated to display numerous beneficial pharmacological activities.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the more an SRE dose increases up to 400 μg/mL, the more proliferation of splenocytes increases and tumor proliferation decreases. There are reports of SRE inducing immunomodulatory effects including inflammatory responses and cytokine production ( 27 , 28 ). Our findings suggest that SRE would not only have a cytotoxic effect on CRC cells but also promote T cell immunity and have anticancer effects via inhibition of PD-1/PD-L1 interaction in splenocyte-tumor coculture systems.…”
Section: Discussionmentioning
confidence: 99%
“…Ziyuglycosides are known as primary terpenoid compounds of S. officinalis that have been reported to exhibit diverse biological actions, including anti-cancer, anti-inflammation, anti-skin aging, anti-hyperlipidemia, and hemostasis properties [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. However, anti-diabetic properties of ziyuglycosides have not been reported yet.…”
Section: Discussionmentioning
confidence: 99%
“…Ziyuglycoside II (ZG02) is a triterpenoid compound isolated from S. officinalis [ 28 ]. Previous studies demonstrated that the methyl ester form of ZG02 (ZG02-ME) plays a significant role in modulating hyperlipidemic conditions [ 29 , 30 , 31 ] and inflammatory responses [ 32 ]. Furthermore, it has been reported that ZG02-ME, which is derivatized from ziyuglycoside I (ZG01) by chemical modification, possesses an improved inhibitory activity in vivo compared with that of ZG01 on tissue factor and tumor necrosis factor (TNF)-α productions [ 33 ].…”
Section: Introductionmentioning
confidence: 99%